PENGARUH PERSEPSI HARGA, DESAIN, KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBEIAN SMARTPHONE SAMSUNG - verry ade frandika (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to describe the effect of perceived price (PH) on purchasing decisions (KB), design (D) on purchasing decisions (KB), product quality (KP) influence on purchasing decisions (KB). and brand image (CM) influence on purchase decision (KB). The population is a student of the Faculty of Economics of Sarjanawiyata Tamansiswa University who is using and using Samsung Smartphone and the sample for this research is needed 100 people. Data completion method was done by using questionnaire, while data analysis technique using multiple regression analysis supported by multicolonierity test, heterokedasitas test, and normality test. The results showed multiple linear regression equations for perceived price(PH), design (D), product quality (KP), and brand image (CM) influence on purchase decision.